(untitled) (Journal of Economic Additions, 2026)
This article examines the digital visibility of Algerian universities, specifically Abou Bekr Belkaïd University (Tlemcen), Maghnia University Center, and Abdelhafid Boussouf University Center (Mila). Using Webometrics indicators (Visibility, Openness, and Excellence), the study performs a comparative analysis of their international rankings. Results reveal significant disparities in digital presence and scientific output, highlighting challenges in academic competitiveness. The study concludes that improving website quality, promoting open-access publishing, and adopting effective digital strategies are essential to enhancing the global visibility of Algerian higher education institutions. Jel Classification codes :I23